Breast reconstruction by pedicled transverse rectus abdominis myocutaneous flap - Kozarski Jefta; Đorđević Boban; Šijan Goran; Stanković Goran; Stanojević Bojan (Vojnosanitetski Pregled)
Reconstruction of the amputated breast in female patients after surgical management of breast carcinoma is possible with the use of autologous tissue, synthetic implants, or by combining autologous tissue and synthetic materials. Autologous tissue provides soft and sufficiently elastic tissue which is usable for breast reconstruction and eventually obtains original characteristics of the surrounding tissue on the chest wall. The use of the TRAM flap for breast reconstruction was introduced in 1982 by Hartrampf Scheflan, and Black. The amount of the TRAM flap tissue allows breast reconstruction in the shape most adequate to the remaining breast. The possibilities of using the TRAM flap as pedicled myocutaneous flap or as free TRAM flap make this flap a superior choice for breast reconstruction in comparison with other flaps.